Optimization of thaumatin extraction by aqueous two-phase system (ATPS) using response surface methodology (RSM) - A.L., Ahmad; C.J.C., Derek; Mohamed Zulkali, Mohamed Daud (Elsevier B.V., 2009)
Link to publisher's homepage at www.elsevier.com